2011
DOI: 10.1017/s0007114511002340
|View full text |Cite
|
Sign up to set email alerts
|

National Diet and Nutrition Survey: UK food consumption and nutrient intakes from the first year of the rolling programme and comparisons with previous surveys

Abstract: The National Diet and Nutrition Survey (NDNS) is a cross-sectional survey designed to gather data representative of the UK population on food consumption, nutrient intakes and nutritional status. The objectives of the present paper were to identify and describe food consumption and nutrient intakes in the UK from the first year of the NDNS rolling programme and compare these with the 2000-01 NDNS of adults aged 19 -64 years and the 1997 NDNS of young people aged 4 -18 years. Differences in median daily food c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
161
3
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(186 citation statements)
references
References 23 publications
(24 reference statements)
15
161
3
3
Order By: Relevance
“…Parents' knowledge of food sources was poor, with a mean (±SD) incorrect response of 76% ±11·2. Contrastingly, 93% correctly identified sunlight exposure as a potential source of vitamin D. Eighty nine percent of participants played outdoors daily for 1 hour or more, 81% used sunscreen with an SPF ≥30 and only 2% rarely applied sunscreen.This study revealed that children's diet in the NW England is lacking sufficient vitamin D content, in line with larger surveys (7,8) . Parents' knowledge regarding vitamin D dietary sources was poor but 93% of parents knew that sunlight was the non-dietary source of vitamin D. Outdoor play indicated sufficient exposure time to produce endogenous vitamin D but sunscreen usage may have potentially diminished epidermal UVB exposures.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Parents' knowledge of food sources was poor, with a mean (±SD) incorrect response of 76% ±11·2. Contrastingly, 93% correctly identified sunlight exposure as a potential source of vitamin D. Eighty nine percent of participants played outdoors daily for 1 hour or more, 81% used sunscreen with an SPF ≥30 and only 2% rarely applied sunscreen.This study revealed that children's diet in the NW England is lacking sufficient vitamin D content, in line with larger surveys (7,8) . Parents' knowledge regarding vitamin D dietary sources was poor but 93% of parents knew that sunlight was the non-dietary source of vitamin D. Outdoor play indicated sufficient exposure time to produce endogenous vitamin D but sunscreen usage may have potentially diminished epidermal UVB exposures.…”
supporting
confidence: 87%
“…This study revealed that children's diet in the NW England is lacking sufficient vitamin D content, in line with larger surveys (7,8) . Parents' knowledge regarding vitamin D dietary sources was poor but 93% of parents knew that sunlight was the non-dietary source of vitamin D. Outdoor play indicated sufficient exposure time to produce endogenous vitamin D but sunscreen usage may have potentially diminished epidermal UVB exposures.…”
supporting
confidence: 87%
“…Protein's contribution to total calorie intake was similar in Brazil, the United States h and the United Kingdom. 29 However, the proportion of lipids was higher in the United States h and the United Kingdom 29 and the proportion of carbohydrates was higher in Brazil than in these two countries. The Mexicans consumed fewer calories derived from protein and more deriving from carbohydrates compared to the Brazilians.…”
Section: Discussionmentioning
confidence: 94%
“…14 Protein's contribution to total calorie intake was similar in Brazil, the United States h and the United Kingdom. 29 However, the proportion of lipids was higher in the United States h and the United Kingdom 29 and the proportion of carbohydrates was higher in Brazil than in these two countries. The Mexicans consumed fewer calories derived from protein and more deriving from carbohydrates compared to the Brazilians.…”
Section: Discussionmentioning
confidence: 94%